Education in Finland: Reflections from a Field Trip Abroad - Debbie Mercer; Lotta Larson (The Advocate, 2013)
Introduction: After hearing much about the Finnish education system, we recently jumped at the opportunity to visit the country to explore schools and education organizations as members of a professional organization tour. In this article, we aim to reflect upon what we learned, provide multiple perspectives of the Finnish education system, and discuss possible implications for Kansas educators.